The ethical implementation of the doctor in Islamic law (مجلة أبحاث قانونية, 2023)
There is no doubt that the work of a doctor is a humanitarian work aboveall else, based on compassion, honesty, and sound purpose. However, someweak souls may deviate from this principle, those with hard hearts and blindminds,whomaketheirconcernandgoalthecollectionofmoneyfrombehind.Thisprofession,andthepreeminenceinsociety,withouttakingintoaccounttheduties thattheymustadheretoit.Soitisofgreatimportancetoalwaysandneverbealerttowhiletheethicalduties that the doctor must adhere to it while performing this honorableprofession, and this is what I wanted to alert through this paper thatI titled it(The Ethical Responsibility of the Physician in Islamic Low), and I dividedthediscussionintotwosections:thefirstdiscussedtheconceptofmoralresponsibility and the foundations upon which it is based, and the secondsectiondealtwiththeethicalcontrolsforthosewhopracticemedicalworkFromthis,Iconcludedmanyconclusions,themostimportantofwhichisthatitisoneofthedutiesTheethicaldoctoristogivethepatienthisfullandundiminished rights, to treat him with kindness, to advise him and be honestindealingwithhim,andtotakeintoaccounthishealth,psychologicalandfinancialconditions,andthathisobtainingcompensationforhismedicalworkislegislatedbylow,butthatshouldnotbethegoalofthedoctorpracticingthis profession, rather it is It is primarily a humanitarian profession, the goalofwhichistohelppeoplepreventillnessfromthembyThe Godwilling.Thisstudyrecommendedtheneedtopayattentiontoraisingyoungchildrenfromayoungagewithsoundmoraleducation,theneedtointroducetheIslamicethicscourseandtheworkethicscourseinthevariousstagesofeducation,andtheneedformedicalauthoritiestostrivetoestablishethicalchartersforworkersinthehealthsector,andtakethenecessarymeasuresandappropriate decisions to activate commitment to them in various areas ofwork.
Keywords: Ethicalresponsibility; physicianresponsibility; physicianethics